2018
DOI: 10.1101/342006
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uneven distribution of cobamide biosynthesis and dependence in bacteria predicted by comparative genomics

Abstract: 20 21The vitamin B 12 family of cofactors known as cobamides are essential for a variety of microbial 22 metabolisms. We used comparative genomics of 11,000 bacterial species to analyze the extent 23 . CC-BY-NC 4.0 International license It is made available under a was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint (which . http://dx.doi.org/10.1101/342006 doi: bioRxiv preprint first posted online Jun. 8, 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…This agrees with previous studies suggesting that cobalamin in the surface ocean may be primarily the result of de novo synthesis by heterotrophic bacteria or via modification of cyanobacteriallyproduced pseudocobalamin, while Thaumarchaeota may be a major cobalamin producer at depth (14). Despite the high abundance of Bacteroidetes in the MES, studies have shown that only 0.6% of Bacteroidetes have complete B12 synthesis pathways (15). Gene families (e.g.…”
Section: Microbial Taxa Carrying B12 Biosynthesis Genes In the Global...supporting
confidence: 91%
See 3 more Smart Citations
“…This agrees with previous studies suggesting that cobalamin in the surface ocean may be primarily the result of de novo synthesis by heterotrophic bacteria or via modification of cyanobacteriallyproduced pseudocobalamin, while Thaumarchaeota may be a major cobalamin producer at depth (14). Despite the high abundance of Bacteroidetes in the MES, studies have shown that only 0.6% of Bacteroidetes have complete B12 synthesis pathways (15). Gene families (e.g.…”
Section: Microbial Taxa Carrying B12 Biosynthesis Genes In the Global...supporting
confidence: 91%
“…Second, consistent with our current knowledge (14), only a few microbial genera in the ocean were found to carry de novo B12 biosynthesis potential by judging the gene families linked to the microbial taxa. However, comparative genomics of currently sequenced microbial genomes from NCBI RefSeq suggest that 37% of prokaryotic microbial species have the potential to biosynthesize cobamides de novo, though complete pathways are not always detected (15). Among these, 57% of Actinobacteria are predicted to biosynthesize cobamides, whereas only 0.6% of Bacteroidetes have the complete pathway (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted November 29, 2023. ; https://doi.org/10.1101/2023.11.29.569236 doi: bioRxiv preprint inhibitory constants for corrinoid-dependent enzymes about 100-fold, suggesting the disruption of metabolic pathways directly or indirectly impacted N2O-consuming populations. Only a subset of bacteria and archaea synthesize corrinoids [86], and corrinoid prototrophs supply this essential nutrient to corrinoid auxotrophs [87,88]. The addition of N2O disrupts these interactions, an effect influenced by the concentration of N2O.…”
Section: Impact Of N2o Concentration On N2o Reductionmentioning
confidence: 99%